Changes of endotracheal tube cuff pressure and its indicators in laparoscopic resection of colorectal neoplasms: an observational prospective clinical trial - Shenquan Cai; Xuan Wang; Jie Zhang; Guangli Zhu; Chenyao Jian; Shanwu Feng; Manlin Duan (BMC Anesthesiology)
Abstract Background Laparoscopic surgery is a popular alternative for resection of colorectal neoplasms. Carbon dioxide pneumoperitoneum and Trendelenburg positioning in procedure can significantly increase airway pressure, when endotracheal tube cuff pressure is not monitored. This prospective observational study aimed to evaluate indicators, changes and its correlation factors of endotracheal tube cuff pressure during laparoscopic resection of colorectal neoplasms. Methods 122 patients scheduled for laparoscopic resection of colorectal neoplasms under propofol/remifentanil total intravenous anesthesia with orotracheal intubation were included. Tracheal tube cuff pressure was monitored continuously by calibrated pressure transducers. The ability of several predictors to predict out-of-range tracheal tube cuff pressure at different time points and its correlation factors were assessed. Results ROC analysis showed that waist-to-hip ratio has the highest AUC for predicting out-of-range tracheal cuff pressure (AUC: 0.86 [95% CI: 0.77–0.95]); Tracheal tube cuff pressure provided by palpation was 41.0 (29.0−53.3) cmH20. Cuff pressure was 33.7 ± 2.9 cmH20 at 15 min and comparable at 30 and 45 min after insufflation, all values were significantly higher than 25 cmH20 (p < 0.001). Multiple linear regression showed tracheal tube cuff pressure was associated with peak airway pressure (p < 0.001). Conclusions Patients with normal BMI undergoing laparoscopic resection of colorectal neoplasms require continuous monitoring and timely adjustments of tracheal tube cuff pressure. Compared with BMI, waist-to-hip ratio is a better predictor of out-of-range tracheal tube cuff pressure. Trial registration Chinese Clinical Trial Registry, identifier: ChiCTR2100054089, Date: 08/12/2021.